Healthcare Providers’ Vaccine Perceptions, Hesitancy, and Recommendation to Patients: A Systematic Review - Cheryl Lin; Jewel Mullen; Danielle Smith; Michaela Kotarba; Samantha J. Kaplan; Pikuei Tu (Vaccines, 2021)
Despite vaccines’ effectiveness in reducing the rate of preventable diseases, vaccine hesitancy has threatened public health and economies worldwide. Healthcare providers’ (HCP) communications and behavior strongly influence patient receptivity and uptake. The goal of this review was to examine HCP vaccine perceptions, knowledge, and reservations and how these attitudes affect their recommendations and vaccination practices. Primary research studies published by 16 September 2020 were searched in PubMed, Web of Science, Embase, CINAHL, and PsycINFO. A 14-item scale was developed for survey study and risk of bias appraisal (SSRBA). In total, 96 papers from 34 countries were included, covering 17 vaccines (HPV and influenza vaccines the most studied). Recommendation was positively associated with provider knowledge and experience, beliefs about disease risk, and perceptions of vaccine safety, necessity, and efficacy. HCP vaccination attitudes and practices varied across specialties, vaccines, and countries; demographic impact was inconclusive. Barriers included anticipation of patient/parental concerns or refusal, lacking clear guidelines, time constraints, and cost. For HPV, vaccines were more often recommended to older, female adolescents and by physicians who discussed sexual health. HCPs are vital advocates for patients and the public, but studies indicated a prevalence of provider hesitancy pertaining to inadequate knowledge, low vaccine confidence, and suboptimal uptake themselves. Improving HCP knowledge and assuring their access to information they deem trustworthy are essential to supporting HCPs‘ role as “trusted messengers” to promote vaccine acceptance.